MENDIDIK MELALUI HATI SEBAGAI STRATEGI MEMBENTUK KARAKTER BANGSA - Sunhaji Sunhaji (Faculty of Humanities, Universitas Jenderal Soedirman, 2018)
This paper discusses the concepts of character education. The character of the nation is one key for the nation to develop. The character of the nation is highly determined by its efforts to continuously improve the character education processes. No character education may be well implanted to the men’s behavior when the heart of the nation is unhealthy. The main key education success of the nation is a healthy heart. The heart should be healthy that good education may be easily implanted and united into an individual who is reflectively and continuously demanded to do the good things. Thus, whatever the education is named by either character education, value education, multicultural education, religious education, or others intended to build the character and behavior of the educational participants may uneasily be realized if not firstly initiated by educating the heart.